Sistem Pendukung Keputusan Pemilihan Calon Penerima Beasiswa dengan Multi Objective Optimization on The Basis of Ratio Analysis - Dewi Kuncorowati; Eko Purwanto; Hanifah Permatasari (Journal of Information System Research (JOSH), 2025)
The selection of scholarship candidates has so far been conducted manually and is not well-documented. The selection process is based on the opinions or personal preferences of the selection team, which can lead to unfairness. There is no consistent standard for evaluating the criteria of scholarship candidates.This study develops a Decision Support System (DSS) for selecting school scholarship candidates using the Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) method. This method is chosen for its ability to handle various qualitative and quantitative evaluation criteria, such as academic achievement, economic conditions, and extracurricular participation. The system is designed to produce candidate rankings objectively and transparently, facilitating fair and accurate decision-making by the school. Testing results indicate that the MOORA-based DSS can provide accurate and consistent recommendations, enhancing the efficiency of the selection process and stakeholder satisfaction. This research also opens opportunities for further development by integrating technologies such as machine learning to enhance system capabilities. The results of this study can assist in determining acceptance of the scholarship